Gestão dos resíduos de construção civil procedentes de pequenas construções no Município de Belém- Pa - LEITE, João Alex Garcia (Universidade Federal do Pará, 2023)
The construction industry is one of the most important sectors to the economic development of Brazil. However, it also causes some of the greatest environmental impacts mainly due to the improper disposal of construction waste (CW) in natural areas and large urban centers. The issue of CW in Belém includes the problematic due to the absence of the Municipal Construction Waste Management Plan (PMGRCC). Of particular note is the daily construction waste generated and improperly disposed of by small companies and individuals, which is very common in Belém. The main objective of this dissertation is to study the current CW management system for small companies and individuals, with the purpose of improving the treatment processes for CW improperly disposed of by small-scale construction sites in the city of Belém. The specific aims include: identification of those involved in the generation, transportation, and final disposal of CW. The research is based on an exploratory, explanatory, qualitative approach and will be restricted to the Municipality of Belém. It will involve field visits to take photographic records, interviews with those involved in the process, and analysis of data from the Municipal Sanitation Department (SESAN) and the Municipal Solid Waste Department (DRES). It is hoped that the results of this research will help facilitate the introduction of an efficient management process for the control, handling, and final disposal of CW in Belém.